2017
DOI: 10.1186/s12929-017-0388-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hypoxia inducible factor 1α and 2α and its association with vitamin C level in thyroid lesions

Abstract: BackgroundCells adapt to hypoxia by transcriptional induction of genes that participate in regulation of angiogenesis, glucose metabolism and cell proliferation. The primary factors mediating cell response to low oxygen tension are hypoxia inducible factors (HIFs), oxygen-dependent transcription activators. The stability and activity of the α subunits of HIFs are controlled by hydroxylation reactions that require ascorbate as a cofactor. Therefore, deficiency of intracellular vitamin C could contribute to HIFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 40 publications
1
19
1
1
Order By: Relevance
“…When considered individually, none of these associations reached statistical significance, but when a HIF pathway score was assigned to each tumor sample by combining the relative expression of HIF-1α or HIF-2α and their target genes, respectively, a significant inverse association between ascorbate and HIF-1 and combined HIF pathways was apparent. We have previously seen this association in endometrial ( 7 ), colorectal ( 8 ) and breast cancer (unpublished data) and a similar relationship has been reported in thyroid cancer ( 9 ). Together with our current results, these data are consistent with the notion that increased ascorbate levels modulate HIF activity by supporting the function of the regulatory hydroxylases, while insufficient supply leads to accumulation and increased transcriptional activity of HIF (Figure 6 ).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…When considered individually, none of these associations reached statistical significance, but when a HIF pathway score was assigned to each tumor sample by combining the relative expression of HIF-1α or HIF-2α and their target genes, respectively, a significant inverse association between ascorbate and HIF-1 and combined HIF pathways was apparent. We have previously seen this association in endometrial ( 7 ), colorectal ( 8 ) and breast cancer (unpublished data) and a similar relationship has been reported in thyroid cancer ( 9 ). Together with our current results, these data are consistent with the notion that increased ascorbate levels modulate HIF activity by supporting the function of the regulatory hydroxylases, while insufficient supply leads to accumulation and increased transcriptional activity of HIF (Figure 6 ).…”
Section: Discussionsupporting
confidence: 82%
“…Ascorbate has therefore been proposed as a potentially useful adjuvant therapy for cancer [reviewed in Wilson et al ( 13 )], but there is currently debate concerning the proposed mechanism of action [reviewed in Vissers and Das ( 14 )]. Moderation of HIF-1 activation appears likely, although current data only demonstrates an association and not causation ( 7 9 ). To date, there are no reports describing the relationship between HIF-2 activity and ascorbate in vivo .…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Supporting this notion, there is growing evidence that HIF1α-dependent tumour growth may be inhibited by ascorbate 78,79 . Ascorbate level was inversely correlated with HIF1α expression in thyroid lesions 80 , and in vitro study showed that ascorbate treatment induced a dose-dependent decrease in expression of HIF1α and GLUT1 (a downstream target of HIF 1) in thyroid cancer cells 80 . In studies with Gulo −/− mice, lung carcinoma implanted in Gulo −/− mice grew slowly when mice were treated with high-dose ascorbate either in drinking water (3.3 g per litre) or daily intraperitoneal injection (1 gkg −1 ) as compared with Gulo −/− mice treated with low-dose ascorbate in drinking water (0.33 g per litre), and tumours exposed to high-dose ascorbate also had reduced expression levels of HIF1α, VEGF and reduced microvessel density compared with control mice [81][82][83] .…”
Section: Targeting Hif1 Signallingmentioning
confidence: 99%
“…Animal studies have shown downregulation of HIF-1α and downstream pro-survival proteins (e.g., glucose transporter 1, vascular epithelial growth factor, and carbonic anhydrase) following administration of oral or parenteral vitamin C ( Figure 1 ) ( Campbell et al, 2015 , 2016a , b ). In human colorectal tumors and other tumors there was an inverse association between tumor vitamin C levels and expression of HIF and related downstream proteins ( Kuiper et al, 2010 , 2014a ; Jozwiak et al, 2017 ), and enhanced disease-free survival was observed in patients who had higher vitamin C levels in their tumors ( Kuiper et al, 2014a ).…”
Section: Q6 What Are the Relevant Mechanisms Of Action Of Ivc?mentioning
confidence: 99%